Tales of a minstrel of Reims in the thirteenth century - Rosenberg, Samuel N.; Pippenger, Randall Todd (The Catholic University of America Press, 2022)
"Scholarly translation of Old French tales into English; an account by an anonymous, thirteenth-century minstrel of historical events, including battles for control of the Holy Land; medieval history dramatizing important events in the lives of Muslim and Christian prominent figures"--